This will not pass eaudiobook Trump, biden and the battle for american democracy. - Martin, Jonathan (Simon & Schuster Audio, 2022)
The "blockbuster" ( The Guardian ) New York Times bestseller, a shocking, definitive account of the 2020 election and the first year of the Biden presidency by two New York Times reporters, exposes the deep fissures within both parties as the country approaches a political breaking point. This is the authoritative, "deeply reported" ( The Wall Street Journal ) account of an eighteen-month crisis in American democracy that will be seared into the country's political memory for decades to come. With stunning, in-the-room detail, New York Times reporters Jonathan Martin and Alexander Burns show how both our political parties confronted a series of national traumas, including the coronavirus pandemic, the January 6 attack on the Capitol, and the political brinksmanship of President Biden's first year in the White House. From Donald Trump's assault on the 2020 election and his ongoing campaign of vengeance against his fellow Republicans to the behind-the-scenes story of Biden's selection of Kamala Harris as his running mate and his bitter struggles to unite the Democratic Party, this book exposes the degree to which the two-party system has been strained to the point of disintegration. More than at any time in recent history, the long-established traditions and institutions of American politics are under siege as a set of aging political leaders struggle to hold together the changing country. Martin and Burns break news on most every page, drawing on hundreds of interviews and never-before-seen documents and recordings from the highest levels of government. This "masterful" (George Stephanopoulos) book asks the vitally important (and disturbing) question: can American democracy, as we know it, ever work again?